Unusual relatives of the multisubunit RNA polymerase. (21st December 2018) - Forrest, David
Abstract : Transcription, the first step of gene expression, is accomplished in all domains of life by the multisubunit RNA polymerase (msRNAP). Accordingly, the msRNAP is an ancient enzyme that is ubiquitous across all cellular organisms. Conserved in absolutely all msRNAPs is the catalytic magnesium-binding aspartate triad and the structural fold it is present on, the double ψ β barrel (DPBB). In-depth bioinformatics has begun to reveal a wealth of unusual proteins distantly related to msRNAP, identified due to their possession of the aspartate triad and DPBB folds. Three examples of these novel RNAPs are YonO of the Bacillus subtilis SPβ prophage, non-virion RNAP (nvRNAP) of the B. subtilis AR9 bacteriophage and ORF6 RNAP of the Kluyveromyces lactis cytoplasmic killer system. While YonO and AR9 nvRNAP are both bacteriophage enzymes, they drastically contrast. YonO is an incredibly minimal single-subunit RNAP, while AR9 nvRNAP is multisubunit bearing much more resemblance to the canonical msRNAP. ORF6 RNAP is an intermediate, given it is a single-subunit enzyme with substantial conservation with the msRNAP. Recent findings have begun to shed light on these polymerases, which have the potential to update our understanding of the mechanisms used for transcription and give new insights into the canonical msRNAP and its evolution. This mini-review serves to introduce and outline our current understanding of these three examples of novel, unusual RNAPs.